Gender differences in risk factors for the 2 year development of sarcopenia in community‐dwelling older adults. Issue 3 (1st April 2022) - Choe, Hun Jee; Cho, Be Long; Park, Yong Soon; Roh, Eun; Kim, Hyeon Ju; Lee, Sam‐Gyu; Kim, Bong Jo; Kim, Miji; Won, Chang Won; Park, Kyong Soo; Jang, Hak Chul
Abstract: Background: Sarcopenia is an age‐related chronic condition that can lead to mobility disabilities. This study aimed to evaluate the risk factors for incident sarcopenia in older Korean adults. Methods: The Korean Frailty and Aging Cohort Study (KFACS) is a multicentre prospective study with a baseline examination in 2016–2017. A prospective follow‐up study was conducted in 2018–2019. Changes in muscle‐related variables were evaluated for subjects aged 70–84 years lacking sarcopenia at baseline. Sarcopenia was diagnosed according to the 2019 updated Asian Working Group for Sarcopenia consensus. Results: Among the 1636 participants (54.4% women, age 75.9 ± 3.7) who did not have sarcopenia at baseline, 101 men (13.5%) and 104 women (11.7%) developed sarcopenia by the follow‐up. Those who developed sarcopenia were older (men, 77.9 ± 3.9 vs. 75.7 ± 3.5, P < 0.001; women, 77.5 ± 4.0 vs. 75.5 ± 3.6, P < 0.001) with a lower body mass index at baseline (men, 23.9 ± 2.4 vs. 24.5 ± 2.9 kg/m 2, P = 0.025; women, 23.7 ± 2.8 vs. 25.2 ± 2.9 kg/m 2, P < 0.001) compared with older adults who remained nonsarcopenic; levels of glycated haemoglobin (men, 6.2 ± 1.0% vs. 5.9 ± 0.8%, P = 0.029) and the homeostasis model assessment of insulin resistance (men, 2.0 ± 1.3 vs. 1.7 ± 1.2, P = 0.022) were higher in men who progressed to sarcopenia but not in women. Development of sarcopenia was associated with older age and the frequency of resistance training (≥2 per week) after adjusting for potential risk factors in men [age, odds ratio (OR) 1.17, 95% confidence interval (CI) 1.10–1.25; frequent resistance training, OR 0.50, 95% CI 0.30–0.82]. In women, advanced age, poor nutritional status, and physical inactivity contributed to the development of sarcopenia (age, OR 1.14, 95% CI 1.08–1.21; mini nutritional assessment short form, OR 0.79, 95% CI 0.70–0.90; moderate to high physical activity, OR 0.57, 95% CI 0.34–0.95). Conclusions: In this 2 year KFACS follow‐up, modifiable risk factors for incident sarcopenia differed between genders. Resistance training (≥2 per week) helped to prevent sarcopenia in these community‐dwelling older men. In older women, adequate nutritional support and being physically active might play a role in preventing progression to sarcopenia.